A PROCESS MODEL OF MANAGEMENT ACCOUNTING CHANGE BASED ON THE INSTITUIONAL THEORY CONTRIBUTIONS - Wanderley, Cláudio de Araújo (Revista de Educação e Pesquisa em Contabilidade (REPeC), 2019)
This paper aims to theorise the complexities of the process of management accounting change from an institutional perspective. Institutional theory has been widely used to study management accounting change. However, the institutional literature on management accounting change is fragmented and disjointed, providing an unstructured picture of dynamics and outcomes of the process of management accounting change. This situation makes the task of explaining the complexity of management accounting change extremely difficult. In this paper we argue that the complexity of management accounting change comprises four key elements: (1) the internal and external pressures for change and the interplay between them; (2) the role of agency; (3) the idiosyncratic internal elements; and (4) the process of institutionalisation. Drawing on institutional theory and these four elements of management accounting change, we developed an integrated framework that is able to capture and examine the macro and micro level dynamics in management accounting change.